Odpowiedź :
(x^2-2x)^3 - (x^2 + 2x)^3 = (x^6 - 6x^5 + 12x^4 - 8x^3) - (x^6 + 6x^5 + 12x^4 + 8x^3) = x^6 - 6x^5 + 12x^4 - 8x^3 - x^6 - 6x^5 - 12x^4 - 8x^3 = -12x^5 - 16x^3
Odpowiedź:
[tex](x^2-2x)^3=(x^2)^3-3*(x^2)^2*2x+3*x^2*(2x)^2-(2x)^3=x^6-6x^5+12x^4-8x^3\\(x^2+2x)^3=(x^2)^3+3*(x^2)^2*2x+3*x^2+(2x)^2+(2x)^3=x^6+6x^5+12x^4+8x^3\\\\(x^2-2x)^3-(x^2+2x)^3=x^6-6x^5+12x^4-8x^3-(x^6+6x^5+12x^4+8x^3)=x^6-6x^5+12x^4-8x^3-x^6-6x^5-12x^4-8x^3=x^6-x^6-6x^5-6x^5+12x^4-12x^4-8x^3-8x^3=-12x^5-16x^3[/tex]
Szczegółowe wyjaśnienie:
[tex](a+b)^3=a^3+3a^2b+3ab^2+b^3\\(a-b)^3=a^3-3a^2b+3ab^2-b^3[/tex]